Cover Image. (5th July 2018) - Thomson, Peter J.; Goodson, Michaela L.; Smith, Daniel R.
Abstract : The cover image, by Peter J. Thomson et al., is based on the Original Article Potentially malignant disorders revisited—The lichenoid lesion/proliferative verrucous leukoplakia conundrum, DOI:10.1111/jop.12716 .